SINKRONISASI MINERALISASI NITROGEN DAN FOSFOR BIOMASA TUMBUHAN DOMINAN DI LAHAN KERING - Riyanto Djoko (Universitas Tribhuwana Tunggadewi, 2006)
An effort to improve nutrients released from decomposing Cassia hirsuta, Centrosema pubescens, Phaseolus lunatus, Psophocarpus tetragonolobus, Mimosa somian and Flemingia congesta was carried out by mixing the plant biomass with farmyard manure locally available at the area. Each type of the biomass was mixed thoroughly with the manure at two levels (10% and 20% by weight). Twelve treatments (six plants biomass and two levels of farmyard manure) were arranged in a Factorial Randomized Block Design with three replicates. Results of the field experiment indicated that the mixture of 80% Cassia hirsuta and 20% manure left the highest amount of N and available P in the soils, whereas the mixtures of 90% Mimosa somian + 10% manure and 90% Centrosema pubescens + 10% manure treatment resulted in the lowest amount of N and available P in the soil, respectively. Application of 80% Centrosema pubescens + 20% manure resulted in the highest amount of N and P taken up by maize at 12 weeks. The highest amount of N and P taken up by maize, whereas the lowest amount of N and P taken up by maize was observed for the mixture of 90% Flemingia congesta +10% manure and the mixture of 90% Centrosema pubescens + 10% manure, respectively. The best synchronization between N released and maize demand for nitrogen was obtained by application of 80% Cassia hirsuta + 20% manure (efficiency of 50,67%), and that of P was obtained by application of 90% Flemingia congesta + 10% manure (efficiency of 74,76%)